2000
DOI: 10.1128/jb.182.23.6762-6773.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Overlapping angB and angG Genes Are Encoded within the trans -Acting Factor Region of the Virulence Plasmid in Vibrio anguillarum : Essential Role in Siderophore Biosynthesis

Abstract: Products encoded in the trans-acting factor (TAF) region are necessary for the biosynthesis of anguibactin and for maximal expression of iron transport and biosynthesis genes in the plasmid-encoded iron-scavenging system of Vibrio anguillarum. Here we identify angB, a locus located in the TAF region, which encodes products essential for anguibactin biosynthesis. We demonstrate that a 287-amino-acid polypeptide, encoded by angB and designated AngB, has an isochorismate lyase activity necessary for the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 52 publications
0
67
0
Order By: Relevance
“…Genetic complementation assays and siderophore utilization tests proved that the A. baumannii dhbA, dhbB and dhbE genes encode active proteins that restore enterobactin biosynthesis and iron uptake proficiency when introduced in E. coli ent mutants. These assays also showed that the dhbB translational product is a bifunctional protein that is required for the biosynthesis of catechol siderophores such as enterobactin (Earhart, 1996) and anguibactin (Crosa & Walsh, 2002;Welch et al, 2000). This chromosomal region, which is part of the pMU73 insert DNA, also includes genes encoding predicted proteins that belong to the EntD and EntF family.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic complementation assays and siderophore utilization tests proved that the A. baumannii dhbA, dhbB and dhbE genes encode active proteins that restore enterobactin biosynthesis and iron uptake proficiency when introduced in E. coli ent mutants. These assays also showed that the dhbB translational product is a bifunctional protein that is required for the biosynthesis of catechol siderophores such as enterobactin (Earhart, 1996) and anguibactin (Crosa & Walsh, 2002;Welch et al, 2000). This chromosomal region, which is part of the pMU73 insert DNA, also includes genes encoding predicted proteins that belong to the EntD and EntF family.…”
Section: Discussionmentioning
confidence: 99%
“…Like EntB, the amino terminus of AngB possesses the isochorismate lyase activity (ICL in Fig. 11A), thereby explaining the need for this protein for the synthesis of DHBA (131). Analysis of mutations in the angB open reading frame provided evidence that in addition to angB, an overlapping gene, angG, exists at this locus and that it encodes three polypeptides which are in frame to the carboxy-terminal end of the 33-kDa AngB.…”
Section: Enzymologymentioning
confidence: 99%
“…Under iron-rich conditions, the Fe 2ϩ -Fur complexes bind to promoters containing a Fur box (Fur binding sequence) and repress transcription. Although Fur is required for transcriptional activation of some genes, this effect may be indirect (12,90,117,131). Fur homologues have been identified in Esche-richia coli and many other Gram-negative bacteria (12,25).…”
Section: Introductionmentioning
confidence: 99%
“…In some V. anguillarum strains, the chromosomal angA gene is present in a cluster with the other DHBA biosynthetic genes since these strains still produce DHBA when cured from the plasmid (174,175). In the case of V. anguillarum 531A, curing of the plasmid abolishes DHBA production, pointing to an incomplete chromosomally encoded DHBA cluster (176). The plasmid also carries the genes for the synthesis of N-hydroxyhistamine from histidine.…”
Section: Anguibactin Biosynthesismentioning
confidence: 99%
“…Activated DHBA is then tethered to the ArCP domain of AngG to further continue its assembly in the anguibactin molecule (100,175,176,179). The angG gene is transcribed from the same promoter as angB and can be found in one polypeptide with AngB but also as a separate polypeptide (176).…”
Section: Anguibactin Biosynthesismentioning
confidence: 99%